Putusan MA Nomor 3459 K/Pdt Mengenai Wanprestasi terhadap Perjanjian Jual Beli Tanah - Elvira Fitriyani Pakpahan; Gail Jevona Juneta Elviani Zebua; Melva Nainggolan (Jurnal Hukum Lex Generalis, 2025)
This case involves a land sale and purchase agreement dispute between the buyer and seller. The buyer (Plaintiff) claims that the seller did not deliver the land certificate as promised in the agreement, then the seller (Defendant) submits an argument that the delivery of the certificate was delayed due to administrative problems which were not his responsibility. The Supreme Court considered that in a sale and purchase agreement, both parties have an obligation to fulfill the agreed provisions. Default occurs if one party does not fulfill its obligations without a valid reason. Therefore, the Supreme Court decided that the seller had committed a breach of contract because he did not hand over the land certificate in accordance with the agreement. As a result, the Supreme Court upheld the decision of the court of first instance which ordered the seller to immediately hand over the land certificate to the buyer and pay the fine as stipulated in the agreement. This decision emphasizes the importance of fulfilling obligations in the land sale and purchase agreement and providing legal protection to parties who suffer losses due to default.